PENGARUH GADGET TERHADAP PERKEMBANGAN SOSIAL ANAK DI TK AISYIYAH BUSTANUL ATHFAL VI - Sinta, Sinta; Ali, Muhamad; Halida, Halida (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is motivated by the use of gadget applications that can affect the social development of children. Based on the data that researchers obtained from kindergarten Aiyiyah Busthanul Athafal VI children who are at school kindergarten 69% of children who use gadgets applications. Therefore, researchers want to see whether the use of gadget applications affect the social development of children. The problem in this study is